2021
DOI: 10.3389/fcvm.2021.691203
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Novel NKX2-5 Mutation in a Family With Congenital Heart Defects, Left Ventricular Non-compaction, Conduction Disease, and Sudden Cardiac Death

Abstract: The NKX2-5 gene encodes for a transcription factor crucial for cardiac cell differentiation and proliferation. It was the first gene associated with congenital heart disease (CHD) in humans and has been linked to conduction disorders or cardiomyopathies. However, an overlapping phenotype is not frequent in the literature. We describe a family with a novel missense mutation in the NKX2-5 gene (p.Gln181Pro) with numerous antecedents with atrial septal defect (ASD), left ventricular non-compaction (LVNC), conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The NKX2-5 gene, located on chromosome 5, plays an important role in cardiac development and maintenance of the normal function of the AV node and myocardium throughout adult life 3–5. Previous literature has suggested that a large proportion of NKX2-5 mutations originate from Europe (24.1%) 6…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NKX2-5 gene, located on chromosome 5, plays an important role in cardiac development and maintenance of the normal function of the AV node and myocardium throughout adult life 3–5. Previous literature has suggested that a large proportion of NKX2-5 mutations originate from Europe (24.1%) 6…”
Section: Discussionmentioning
confidence: 99%
“…NKX2-5 mutations have also been reported in patients with dilated cardiomyopathy and left ventricular non-compaction (LVNC) 3 10 11. Yamada et al 11 identified a novel heterozygous NKX2-5 variant (NM_004387.1: c.255_256delCT, p.Phe86fs) in a girl in early adolescence with previous ASD repair, who presented with exertional syncope and was found to have AV block and LVNC on echocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several inactivating mutations in the NKX2-5 gene, primarily located within the homeodomain, have been described in patients with a spectrum of congenital heart diseases (CHD), the most frequent ones being atrial or ventricular septal defects and tetralogy of Fallot (2). In addition, NKX2-5 pathogenic variants have been reported in adult patients with heart conduction defects such as atrial fibrillation (3) and, more recently, with sudden cardiac death from ventricular arrhythmia (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%